Electric Vehicles Powered by Renewable Energy: Economic and Environmental Analysis from the Brazilian Perspective - Castro, Thais Santos [UNESP]; Moura, Carlos Henrique Silva [UNESP]; Silveira, José Luz [UNESP]; de Souza, Teófilo Miguel [UNESP] (MDPI, 2025)
The concern for sustainability, understood as the responsible use of natural resources to ensure the well-being of future generations, has grown across various sectors. One of the main drivers of environmental degradation is the use of fossil-fuel-based transportation, which produces pollutant emissions and contributes to climate change. In this context, electric cars have emerged as a smart and sustainable alternative, as they do not emit polluting gases and, when powered by renewable energy sources such as photovoltaics, can significantly reduce the carbon footprint. Based on this concept, it is noted that electric cars are an intelligent alternative to reduce the degradation caused by fossil fuels. The generation of electricity from renewable sources, such as photovoltaics, biogas and others, combined with the low maintenance costs and long service life of these technologies, represents an extremely sustainable solution. In this work, methodologies are applied for sizing and analysis of the cost of electricity generation through photovoltaic energy. The operational cost of the electric car being fueled by electricity provided by this source and by energy from the utility grid compared to the operational cost of an internal combustion engine car is also considered. The (CO2)eq emitted by the use of the photovoltaic plant, energy from the grid and the gasoline used in the internal combustion engine car is also determined. It is concluded that the return on investment for the energy generated by photovoltaic energy is approximately 5 years. The annual cost for an electric car is 76.49% lower when using electricity provided by energy concessionaires in Brazil and 81.35% lower for energy from photovoltaic plants compared to an internal combustion engine vehicle, also considering that the harm to the environment is low for this technology. These data emphasize the importance of looking for technological and sustainable solutions that adapt energy production systems, reduce costs and, above all, help to mitigate the impact on the environment, reflecting a commitment to the future of our planet and the quality of life of future generations.
Keywords: carbon dioxide equivalent; electric vehicle; photovoltaic; renewable energy; sustainability